2005
DOI: 10.1177/070674370505001209
|View full text |Cite
|
Sign up to set email alerts
|

L'évaluation normalisée et clinique des mécanismes de défense: Revue critique de 6 outils quantitatifs

Abstract: Mots Clés : mécanismes de défense, psychométrie, échelles d'évaluation cliniquePour le DSM-IV, « les MD sont des processus psychologiques automatiques qui protPgent l'individu de l'anxiété ou de la perception de dangers ou de facteurs de stress internes ou externes. Les individus n'ont généralement pas conscience de ces processus lorsqu'ils sont B l'Éuvre » (6). L'origine, le développement et l'évolution des MD sont mal connus ainsi que les liens existant entre eux.L'évaluation des MD a longtemps reposé sur la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Based on the transcriptions of the consultations, 30 defences were coded, total number of defences and number of mature and immature defences were calculated, as well as an ODF score ranging from 1 (lowest or most immature defensive functioning) to 7 (highest or most mature defensive functioning). In a critical review of the psychometric characteristics of different measures of defence mechanisms, the Defence Mechanism Rating Scale was found to have a good validity (discriminant, convergent, construct, and concurrent) and reproducibility . Detailed information on the development of the DMRS‐C and its psychometric qualities as well as on the process of coding defences for this study are reported elsewhere .…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the transcriptions of the consultations, 30 defences were coded, total number of defences and number of mature and immature defences were calculated, as well as an ODF score ranging from 1 (lowest or most immature defensive functioning) to 7 (highest or most mature defensive functioning). In a critical review of the psychometric characteristics of different measures of defence mechanisms, the Defence Mechanism Rating Scale was found to have a good validity (discriminant, convergent, construct, and concurrent) and reproducibility . Detailed information on the development of the DMRS‐C and its psychometric qualities as well as on the process of coding defences for this study are reported elsewhere .…”
Section: Methodsmentioning
confidence: 98%
“…In a critical review of the psychometric characteristics of different measures of defence mechanisms, the Defence Mechanism Rating Scale was found to have a good validity (discriminant, convergent, construct, and concurrent) and reproducibility. [26][27][28] Detailed information on the development of the DMRS-C and its psychometric qualities as well as on the process of coding defences for this study are reported elsewhere. 6,10 The first author of this manuscript coded all the consultations.…”
Section: Defence Mechanismsmentioning
confidence: 99%
“…At present there is no comprehensive scale to empirically measure psychotic defense mechanisms. To remedy this lack, we propose such a scale: the P-DMRS (Psychotic-Defense Mechanism Rating Scales), modeled after the DMRS (Defense Mechanism Rating Scales), currently recognized as the gold standard when measuring defensive functioning (Soultanian et al 2005).…”
Section: A P R O P O S E D E M P I R I C a L S C A L E F O R M E A S U R I N G P S Yc H O T I C D E F E N S E M E C H A N I S M Smentioning
confidence: 99%
“…В Канада са извлечени норми по скалите със защитните стилове -средно аритметични и стандартни отклонения, но не са посочени норми по скала Лъжа (Bond, 1984;Bond & Wesley, 1996). DSQ 88 е създаден на основата на психоаналитичната теория и DSM-III-R (Soultanian, Dardennes, Mouchabac, & Guelfi 2005). Валидността на методиката е проверявана чрез експертна оценка от трима психоаналитици всеки айтем какво мери.…”
unclassified
“…В по-кратките версии на въпросника не се включват айтеми от скала Лъжа (Schauenburg et al, 2007;Zeigler-Hill & Pratt, 2007;Bond, 2004;Soultanian et al, 2005).…”
unclassified